System failures in public sector innovation support measures: The case of Estonian innovation system and dairy industry - Dorel Tamm (OrdnungsPolitisches Portal (OPO), 2010)
The external and internal context of the firms is influenced by governmental interventions. For a long time the discussion over government interventions to the market processes and economic environment has taken place. It is accepted by different researchers including supporters of social market economy that some interventions are necessary to create general framework for and achieve desirable outcomes of economic processes through laws, regulations etc. There are different approaches discussing whether and how strongly government should intervene. Reasons for and circumstances in what public sector should intervene and weather the intervention itself creates additional failures or not have mainly been rested on two concepts: market and system failures (Edler, Georghiou 2007: 952).
Keywords: 330; Innovation Molkereiindustrie; Estland; Innovationspolitik; Milchverarbeitung; Staatsversagen; Estland